PERBANDINGAN RASIO KELAMIN, MORTALITAS DAN PERTUMBUHAN IKAN NOMEI (Harpadon nehereus) YANG BERASAL DARI HASIL PENANGKAPAN NELAYAN JUATA KOTA TARAKAN - Perdana, Indra; Salim, Gazali; Weliyadi, Encik (Jurnal Harpodon Borneo, 2016)
The aim of research was to determine the sex ratio test; fish mortality and growth of fish nomei in waters Juata Tarakan City. Method location research is purposive sampling with consideration that the research sites is the main area of fishing nomei in the waters Juata Tarakan City. The variable in this study is the variable sex ratio, mortality, growth allometri, condition index, absolute growth, age structure. Sample collection technique using field surveys. The sampling method by using the technique of